SOSIALISASI DAN EDUKASI PENCEGAHAN KEBAKARAN HUTAN KEPADA KELOMPOK TANI HUTAN DI NEGERI HUTUMURI KECAMATAN LEITIMUR SELATAN PULAU AMBON - John F. Sahusilawane; Wilma N. Imlabla (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2026)
Forest fires in the Ambon Island region, particularly in Hutumuri Village, South Leitimur District, Ambon City, pose an environmental threat influenced by climate change, particularly during the dry season, land burning, and low public awareness, as documented in reports from the National Disaster Management Agency and the Ministry of Environment and Forestry's fire prevention policies. This outreach and education activity aims to increase public knowledge and participation through outreach, discussions, and initial fire response simulations, primarily targeting village officials, community leaders, and youth groups. The results demonstrate increased understanding, changes in attitudes toward environmental stewardship, and a collective commitment to mitigation efforts. The outreach and education activities demonstrate that the community is consciously, willingly, and on their own initiative, as well as as a group, willing to take effective and sustainable forest fire prevention measures.